2015
DOI: 10.1292/jvms.15-0200
|View full text |Cite
|
Sign up to set email alerts
|

Endostatin inhibits bradykinin-induced cardiac contraction

Abstract: .Endogenous fragments of extracellular matrix are known to possess various biological effects. Levels of endostatin, a fragment of collagen type XVIII, increase in certain cardiac diseases, such as cardiac hypertrophy and myocardial infarction. However, the influence of endostatin on cardiac contraction has not been clarified. In the present study, we investigated the effects of endostatin on bradykinin-induced atrial contraction. Isometric contractile force of mouse isolated left atria induced by electrical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…89) We have shown that endostatin inhibits the T-type calcium channel expressed in a ventricular cardiomyocyte from guinea pig, and in a hypertrophied cardiomyocyte from the right ventricle of monocrotalineinduced pulmonary hypertensive rat. 120,121) We also showed that a knockdown of the collagen XVIII (endostatin) gene by siRNA-treatment decreases the survival rate and exacerbates the monocrotaline-induced right ventricular remodeling. 121) Thus, the cardioprotective effect of endostatin might be ex-erted through the inhibition of T-type calcium channel activity.…”
Section: Perspectives On the Roles Of Basement Membrane-derived Matrimentioning
confidence: 93%
See 4 more Smart Citations
“…89) We have shown that endostatin inhibits the T-type calcium channel expressed in a ventricular cardiomyocyte from guinea pig, and in a hypertrophied cardiomyocyte from the right ventricle of monocrotalineinduced pulmonary hypertensive rat. 120,121) We also showed that a knockdown of the collagen XVIII (endostatin) gene by siRNA-treatment decreases the survival rate and exacerbates the monocrotaline-induced right ventricular remodeling. 121) Thus, the cardioprotective effect of endostatin might be ex-erted through the inhibition of T-type calcium channel activity.…”
Section: Perspectives On the Roles Of Basement Membrane-derived Matrimentioning
confidence: 93%
“…120,121) We also showed that a knockdown of the collagen XVIII (endostatin) gene by siRNA-treatment decreases the survival rate and exacerbates the monocrotaline-induced right ventricular remodeling. 121) Thus, the cardioprotective effect of endostatin might be ex-erted through the inhibition of T-type calcium channel activity. Collectively, it is conceivable that basement membranederived matricryptins are likely endogenous cardioprotective peptides.…”
Section: Perspectives On the Roles Of Basement Membrane-derived Matrimentioning
confidence: 93%
See 3 more Smart Citations